2020
DOI: 10.1039/d0an01206h
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing glycans cleaved from a biotherapeutic protein using ultrahigh-resolution ion mobility spectrometry together with cryogenic ion spectroscopy

Abstract: A new approach for analysis of cleaved glycans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Furthermore, most diagnostic features in glycan IR spectra from our laboratory 37 , 40 , 41 , 46 , 60 are observed in a wavenumber range from 3580 to 3680 cm –1 , which is also supported by the success of the PCA and clustering method applied to a reduced wavenumber range as described above. An identifying fingerprint of the GalNAc-α(1-3)-Gal-OMe ions can thus be recorded in as little as 5 s without losing its most unique identifying features.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, most diagnostic features in glycan IR spectra from our laboratory 37 , 40 , 41 , 46 , 60 are observed in a wavenumber range from 3580 to 3680 cm –1 , which is also supported by the success of the PCA and clustering method applied to a reduced wavenumber range as described above. An identifying fingerprint of the GalNAc-α(1-3)-Gal-OMe ions can thus be recorded in as little as 5 s without losing its most unique identifying features.…”
Section: Resultssupporting
confidence: 72%
“…Our group has previously demonstrated that high-resolution IMS combined with cryogenic infrared (IR) spectroscopy can unambiguously distinguish between structurally related glycan isomers, 37 39 and we have recently reported structure-specific IR fingerprints for glycans consisting of up to 10 monosaccharides. 40 The robustness and accuracy of this technique is based on the fact that an IR spectrum is an intrinsic property of the analyte molecule and requires neither continuous calibration of the instrument nor internal standards. Once recorded and stored in a database, an IR fingerprint serves as a unique identifier that can be reproduced across laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…In a proof-of-principle experiment conducted by Ben Faleh, Warnke, & Rizzo (2019) , the SLIM-IMS integrated with cryogenic IR-MS displayed ultrahigh resolution and was powerful enough to identify the composition of isomers mixtures, compared with drift-tube IMS. With this ultrahigh resolution, characteristic fingerprints for a series of larger carbohydrates, ranging from heptasaccharide to decasaccharide, were provided ( Yalovenko, Yatsyna, Bansal, AbiKhodr, & Rizzo, 2020 ). The generality of anomeric retention during CID of carbohydrates was also investigated by cryogenic IR-MS conducted by Pellegrinelli et al (2020) .…”
Section: Advanced Ir Techniques and Their Applicationsmentioning
confidence: 99%
“…The combination of IR fingerprinting with SLIM-based ultrahigh-resolution cyclic IMS was subsequently demonstrated to be a powerful tool for the analysis of glycan mixtures. [41][42][43][44] However, any identification method that relies on a database, such as IR spectral fingerprinting, requires access to pure analytical standards. For many complex glycan structures, such standards are either expensive to synthesize or unavailable, which raises the need to create reference data from glycans in isomeric mixtures.…”
Section: Introductionmentioning
confidence: 99%